STRES MAHASISWA SAAT PENYUSUNAN KARYA TULIS ILMIAH DI POLTEKKES MAJAPAHIT MOJOKERTO - PUSPITANINGSIH, DWIHARINI (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2015)
Stress is a reaction due to mental stress or load life unable to be processed and ended by the health and function of organs. One of the causes of students stress that affect graduation is the preparation of scientific papers. For the students, is not easy task. The purpose of this study is to determine the incidence of stress in the preparation of scientific papers On D3 Nursing Student in Poltekkes Majapahit Mojokerto The type of this study is descriptive, byusing a total sampling as many as 127 students then will be taken by 117 sampling, the instrumentis a questionnaire. The data will be processed by editing, coding, scoring, tabulating and presented in the form of a frequency distribution table. The results showed that 19 respondents have normal stress (16.2%), 22 respondents have mild stress (18,8%), 26 respondents have middle stress (22.2%), 27 respondents have severe stress (23,0 %), 23 respondents have very serious stress (19,6 %). The conclusions in this study, stress that occurs in students not only psychological stress but also physical stress, so that students easily feel tired, fatigue, and excessive anxiety when they exam scientific papers. The program of mental health, such as counseling, is so needed to the students for the paper adaptation in the environmental changes.Key words : Stress, Student, Scientific Writing